New specimens and supplementary descriptions of two rare dragonfishes, Photonectes klepadloae and P. litvinovi, with comments on the distribution of P. filipendulus (Teleostei: Stomiidae: Melanostomiinae) - Prokofiev, Artem M.; Frable, Benjamin W. (Zootaxa, 2023)
Supplementary descriptions based on new specimens of two rare dragonfish species, Photonectes klepadloae and P. litvinovi, formerly known by the holotypes only, are presented. The presence of a bulbous swelling at the tip of the terminal filament of the mental barbel is documented for P. klepadloae, and its absence in some specimens of that species, including the holotype, is likely an artifact of preservation. The presence of blue luminous tissue is documented for P. litvinovi, which was formerly believed to lack it due to skin abrasion in the holotype. A key for the species is corrected based on the new diagnostic characters of P. litvinovi. Incorrect mapping of the distribution of P. filipendulus provided in the original description is improved and a map showing the known distribution of all three aforementioned species is presented.